Sustainability and people in international management : 21st century challenges - Volfová, Jitka, 1982-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (Praha : VŠE, Nakladatelství Oeconomica, 2025)
This scientific monograph describes new research findings on chosen International Management challenges connected to Human Resources and Sustainable Work Environment in the 21st century. It mentions best practices for managers and leaders who can get inspired when creating a sustainable working environment, treating people in organisations sustainably, and being ready to report about it. Just as we invest in and care for natural resources, it is crucial to care about human resources responsibly.
Tato vědecká monografie se věnuje vybraným výzvám mezinárodního managementu 21. století spojeným s lidskými zdroji a udržitelným pracovním prostředím. Popisuje nové vědecké poznatky a osvědčené kroky vedoucí k udržitelnosti lidských zdrojů a udržitelnému pracovnímu prostředí. Předkládá tak inspiraci pro manažery v oblasti péče o lidské zdroje a zpracování zprávy o udržitelnosti. Stejně jako investujeme do přírodních zdrojů a staráme se o ně, je klíčové zodpovědně pečovat o lidské zdroje.
Nad názvem: Prague University of Economics and Business
Na obálce nad názvem: Faculty of International Relations
Obsahuje bibliografické odkazy a rejstřík
Keywords: personální management; lidský kapitál; teleworking; interkulturní komunikace; udržitelný rozvoj; udržitelnost lidských zdrojů; udržitelné pracovní prostředí; monografie; učebnice vysokých škol; personnel management; human capital; teleworking; intercultural communication; sustainable development; monographs; textbooks (higher)